Textbook of Rapid Response Systems Concept and Implementation - DeVita, Michael A.; Hillman, Ken.; Bellomo, Rinaldo; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Textbook of Rapid Response Systems is designed to assist the medical practitioner or administrator to implement and improve a Rapid Response System, from the logistics of creating a Rapid Response System (including resource allocation, process design, workflow, and training), to the problem of patient safety and quality of care, the evaluation of program results, and engagement in systems research. Written by the world$1 (Bs leading innovators in the development of Rapid Response Systems, this brand new book takes the place of its groundbreaking predecessor, DeVita, Hillman, and Bellomo, eds., Medical Emergency Teams (Springer, 2006) and includes coverage of pediatric response systems and sepsis response teams, as well as advice, tips, and process guidelines from successful Rapid Response Systems. Textbook of Rapid Response Systems is an invaluable resource for healthcare professionals seeking to improve quality of care in the emergency setting.s
Section I: RRS$1 (Bs and Patient Safety -- Rapid Response Systems History and Terminology -- RRS$1 (Bs General Principles -- Measuring and Improving Safety -- Integrating a Rapid Response System into a Patient Safety Program -- Acute Hospitalist Medicine and the Rapid Response System -- Medical Trainees and Patient Safety -- Rapid Response Systems: A Review of the Evidence -- Health Care Systems and Their (Lack of) Integration -- Creating Process and Policy Change in Health Care -- The Challenge of Predicting in Hospital Cardiac Arrests and Deaths -- The Meaning of Vital Signs -- Matching Illness Severity with Level of Care -- Causes of Failure to Rescue -- Section II. Creating a RRS -- Impact of Hospital Size and Location on Feasibility of RRS -- Barriers to the Implementation of RRS -- An Overview of the Afferent Limb -- The Impact of Delayed RRS Activation -- The Case for Family Activation of the RRS -- RRT: Nurse-led RRS$1 (Bs -- MET: Physician-led RRS$1 (Bs -- Pediatric RRS$1 (Bs -- Sepsis Response Team -- Other Efferent Limb Teams: (BAT, DAT, M, H, and trauma) -- Other Efferent Limb Teams: Crisis Response for Obstetric Patients -- Personnel Resources for Responding Teams -- Equipment, Medications, and Supplies for a RRS -- The Administrative Limb -- The Secondary Victim -- Section III. Monitoring of Efficacy and New Challenges -- RRS$1 (Bs in Teaching Hospitals -- The Nurse$1 (Bs View of RRS$1 (Bs -- Resident Training and RRS$1 (Bs -- Optimizing RRS$1 (Bs Through Simulation -- Evaluating Effectiveness of Complex System Interventions -- RRS Education for Ward Staff -- Standardized Process and Outcome Assessment Tool -- The Impact of RRS$1 (Bs on Choosing (3z(BNot For Resuscitation(3y (BStatus -- The Costs and the Savings.s
Keywords: Medicine; Anesthesiology; Emergency medicine; Critical care medicine; Cardiology; Medicine & Public Health; Intensive / Critical Care Medicine; Emergency Medicine; Anesthesiology; Cardiology